Earth as a sustainable material for conservation - Guerrero, Luis Fernando (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
Earth is a highly durable building material as evidenced by the heritage that has reached our days in remarkable conservation conditions throughout the world. For that reason, its possible application both for the conservation and restoration of properties originally built with soil, as for a wide range of buildings is so important. Earthen construction techniques are fully sustainable from the environmental, economic and socio-cultural perspectives. Soil is an abundant material, easy to use, compatible with most of building systems and it balances the temperature of spaces. In addition, through its correct handling, it is possible to increase or decrease its durability and mechanical and humidity resistance, according to required uses. It can be applied as a sacrificial surface, desiccant, salts eliminator, filling of holes, binder and reinforcement, from proper stabilization and application processes.